Nursing precautions in protecting the lesion from retinopathy associated with diabetes - Theoretical approach (Research, Society and Development, 2023)
The present study aimed to investigate and understand the importance of nurses in the prevention of diabetic retinopathy, in order to encourage further studies on this topic. Therefore, the materials and methods used were based on a theoretical approach, adopting as parameters secondary sources on the subject such as LILACS (Latin American and Caribbean Literature in Health Sciences), SciELO (Scientific Electronic Library Online) and BDENF (Base of Nursing Data). The diabetic patient's lifestyle, including factors such as sedentary lifestyle, diet and even the way he controls his glycemic levels through treatment, influence the complications arising from DM. The nursing professional is of fundamental importance in the care and assistance, during the nursing consultation, performing the reception, data collection and anamnesis, physical examination, tests, in addition to health education. The treatment of people with diabetes should include actions that promote changes in lifestyle, both for patients and their families, who often need guidance to guide them about the reality of the disease. Actions to prevent habits that are modifiable are essential for good control of the disease and prevention of retinopathy.